1967
DOI: 10.1172/jci105662
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Paroxysmal Nocturnal Hemoglobinuria Erythrocytes: Increased Lysis and Lipid Peroxide Formation by Hydrogen Peroxide*

Abstract: Abstract. When paroxysmal nocturnal hemoglobinuria (PNH) erythrocytes were exposed to H202 they lysed excessively and formed greater than normal quantities of lipid peroxides when compared to red cells of normal subjects and patients with most types of hematologic disease. It was also shown that lytic sensitivity to acidified serum was related to the enhanced lytic sensitivity to H202. If the lipid of PNH cells was first extracted then exposed to ultraviolet radiation more lipid peroxides were formed than in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 44 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…The proposed chemical mechanisms by which the sulfydryl com pounds act for the transformation of normal erythrocytes to PNH-like cells include the peroxidation of membrane lipid and the split of mem brane protein disulfide bonds (-S=S-) by reducing them to sulfydryls (-SH) or forming mixed disulfides with them [6,13,23], That lipid perox idation may be involved for the induction of PNH-like cells by these com pounds was suggested by the observations of M engel et al [14], who found that similarly to red cells from their 14 patients with PNH, PNH-like red cells produced by treatment with GSH showed an increased susceptibility to lysis by H20 2 and formed abnormally great quantities of lipid peroxides during incubation with this agent or during exposure to ul traviolet radiation [13,16). Increased susceptibility to autoxidation of red cell lipids was also found by Russian authors [11] both in their 20 cases of PNH and in PNH-like cells produced after treatment with proteolytic enzymes or GSH, by Stocks et al [24] in their sole case of PNH, and by us in one case we had the opportunity to study; P aniker et al [18], how ever, failed to confirm this finding in their 5 PNH patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed chemical mechanisms by which the sulfydryl com pounds act for the transformation of normal erythrocytes to PNH-like cells include the peroxidation of membrane lipid and the split of mem brane protein disulfide bonds (-S=S-) by reducing them to sulfydryls (-SH) or forming mixed disulfides with them [6,13,23], That lipid perox idation may be involved for the induction of PNH-like cells by these com pounds was suggested by the observations of M engel et al [14], who found that similarly to red cells from their 14 patients with PNH, PNH-like red cells produced by treatment with GSH showed an increased susceptibility to lysis by H20 2 and formed abnormally great quantities of lipid peroxides during incubation with this agent or during exposure to ul traviolet radiation [13,16). Increased susceptibility to autoxidation of red cell lipids was also found by Russian authors [11] both in their 20 cases of PNH and in PNH-like cells produced after treatment with proteolytic enzymes or GSH, by Stocks et al [24] in their sole case of PNH, and by us in one case we had the opportunity to study; P aniker et al [18], how ever, failed to confirm this finding in their 5 PNH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many factors claimed to be involved in the PNH corpuscu lar defect, rendering the red cell susceptible to damage and lysis, is in creased vulnerability of the red cell lipids to autoxidation [13,14,16], but the contribution of this factor has been doubted [18].…”
mentioning
confidence: 99%
“…The efforts to define the nature of membrane defect leading to an increase in complement lysis sensitivity seem to be concentrated in two areas. One is concerned with the concept that lipid of PNH red cell membranes may be abnormal either quantitatively (Munn and Crosby 1957) or qualitatively with regard to peroxidation (Meriwether et al 1968;Mengel and Kann 1965;Mengel et al 1967). The other is concerned with the PNH red cell membrane proteins, especially the abnormalities of sulfhydryl and/or disulfide groups (Sirchia et al 1965;Canellos et al 1970;Sandre et al 1970;Mengel et al, 1972;Atlas et al 1973).…”
Section: Morphology Of Ghostsmentioning
confidence: 99%
“…Intrinsic alterations have been demonstrated in the membrane consti tution of those cells as: low levels of acetyl cholinesterase in erythrocytes [18], differ ences in the red cell stroma lipid content [19], increased susceptibility to hydrogen peroxide [17], and low activity of the neu trophil alkaline phosphatase [2], These facts suggest the establishment within the bone marrow of an abnormal clone of pluripotential stem cells, presuma bly following a somatic mutation.…”
Section: Introductionmentioning
confidence: 99%